Metatriangulation: Building Theory from Multiple Paradigms - Lewis, Marianne W.; Grimes, Andrew I. (Academy of Management Review, 1999)
Multiparadigm approaches aid exploration of particularly complex and paradoxical phenomena by helping theorists employ disparate theoretical perspectives. In this article we provide an extensive guide to multiparadigm exemplars and then link their varied approaches within a metatriangulation theory-building strategy. Our process addresses the challenges theorists face as they select a research topic, collect and analyze data, theorize, and evaluate resulting theory using multiple paradigms. A concluding discussion of the advantages, limitations, and potential applications of metatriangulation positions it within the wider realm of organization theory.